Animating Empire : Automata, the Holy Roman Empire, and the Early Modern World - Keating, Jessica, 1979- (Book collections on Project MUSE., 2018)
"Recounts the histories of German clockwork automata, which were given as gifts and collected in the Holy Roman Empire, the Ottoman Empire, and Mughal Empire in the sixteenth and seventeenth centuries"--Provided by publisher